Research on Financial Management Issues from the Perspective of Business and Finance Integration - Bao, Jinjing (Journal of Global Economy, Business and Finance, 2025)
Digital transformation is not merely about enterprises obtaining data, but rather about shifting the operational logic of business modules towards a digital direction. Against this backdrop, the digitalization of enterprise financial systems also requires the overall planning of existing business processes to provide more financial considerations for addressing the issues of enterprise digital transformation. This study mainly conducts research on the deep integration of business and finance in enterprises under the background of digitalization, analyzes the transformation direction of enterprise financial management under the background of business and finance integration, and provides more efficient and intelligent financial management suggestions for enterprises. Solve many problems in the current enterprise financial management, such as talent shortage, unsuitable organizational structure and low data quality. The research suggests that enterprises need to further strengthen the construction of strategic structure, coordinate the financial management and business management of the enterprise, enhance the identification of business risks during the financial management process, and strengthen the construction of integrated data to improve the unity of business and finance integration and promote the transformation of enterprise financial management.